American triatomine species occurrences: updates and novelties in the DataTri database - Ceccarelli, Soledad (2022)
The causative agent of Chagas disease (Trypanosoma cruzi) is transmitted to mammals, including humans, mainly by insect vectors of the subfamily Triatominae (Hemiptera: Reduviidae). Also known as “kissing bugs”, the subfamily currently includes 157 validated species (154 extant and three extinct), in 18 genera and five tribes. Here, we present a subdataset (7852 records) of American triatomine occurrences; an update to the most complete and integrated database available to date at a continental scale. New georeferenced records were obtained from a systematic review of published literature and colleague-provided data. New data correspond to 101 species and 14 genera from 22 American countries between 1935 and 2022. The most important novelties refer to (i) the inclusion of new species, (ii) synonymies and formal transferals of species, and (iii) temporal and geographical species records updates. These data will be a useful contribution to entomological surveillance implicated in Chagas disease.